PERCEIVED IMPACT OF QUALITY OF KASHMIRI ART AND CRAFTS: AN EMPIRICAL STUDY - Dada, Zubair Ahmad; Quisar, Rabia; Lone, Mushtaq Ahmad; Kakroo, Nisar Ahmad; Qureshi, Reyaz A (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Kashmir region is known for its handicraft industry all over the world. The purpose of this study is to determine the impact of the quality of Kashmiri handicrafts on satisfaction and repurchasing intention. The present study is descriptive and convenience sampling method was employed. The data was collected at Srinagar the summer capital of Jammu and Kashmir. The structured questionnaire was distributed among 80 tourists. The findings of this study revealed, there is a strong and positive relationship between the quality of Kashmiri handicrafts, satisfaction, and repurchasing intention. The study verified all the hypotheses using the path coefficient method. Impact of quality of Kashmiri handicrafts on satisfaction and repurchasing intention and lastly the impact of satisfaction on repurchasing intention were found to be statistically significant. Furthermore, the study explores the role of satisfaction in mediating the relationship between the quality of Kashmiri handicrafts and repurchasing intention.